METHODOLOGY FOR TEACHING ENGLISH ONLINE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Increasing student motivation is also important in the teaching process. The online teaching methodology allows students to increase motivation by providing a variety of interactive and engaging activities. Teachers can encourage their students to compete and test their knowledge. For example, through games, quizzes, and other interactive activities, students can test their knowledge and learn new materials in an interesting way. These techniques increase students ' interest and encourage them to read.